Quantitative proteomics reveals novel interaction partners of Rac1 in pancreatic β-cells: Evidence for increased interaction with Rac1 under hyperglycemic conditions() - Damacharla, Divyasri (Mol Cell Endocrinol, 2019)
Rac1, a small G protein, regulates physiological insulin secretion from the pancreatic β-cell. Interestingly, Rac1 has also been implicated in the onset of metabolic dysfunction of the β-cell under the duress of hyperglycemia (HG). This study is aimed at the identification of interaction partners of Rac1 in β-cells under basal and HG conditions. Using co-immunoprecipitation and UPLC-ESI-MS/MS, we identified 324 Rac1 interaction partners in INS-1832/13cells, which represent the largest Rac1 interactome to date. Furthermore, we identified 27 interaction partners that exhibited increased association with Rac1 in β-cells exposed to HG. Western blotting (INS-1832/13 cells, rat islets and human islets) and co-immunoprecipitation (INS-1832/13 cells) further validated the identity of these Rac1 interaction partners including regulators of GPCR-G protein-effector coupling in the islet. These data form the basis for future investigations on contributory roles of these Rac1-specific signaling pathways in islet β-cell function in health and diabetes.